Comparison of different test protocols to determine maximal lactate steady state intensity in swimming - Keller, S.; Manunzio, C.; Wahl, P. (Journal of Science and Medicine in Sport, 2022)
Objectives: This study compared step test, lactate minimum (LM) test and reverse lactate threshold (RLT) test protocols with maximal lactate steady state (MLSS) in free-swimming. All test protocols used fixed duration increments and high work-rate resolution (= 0.03m·s-1) to ensure high sensitivity. Design: Validation study. Methods: 23 swimmers or triathletes (12 male and 11 female) of different ages (19.0±5.9yrs) and performance levels (400m personal best 1.38±0.13m·s-1, FINA points 490±118) completed an incremental step test (+0.03m·s-1 every 3min) to determine speed at 4mmol·L-1 and at modified maximal distance method, a LM test, a RLT test and two to five 30min tests (±0.015m·s-1) to determine MLSS. Following a 200m all-out and a 5min rest, LM was determined during an incremental segment (+0.03m·s-1 every 2min) as the nadir of the speed-lactate curve. After a priming segment with four increments (+0.06m·s-1), RLT was determined as the lactate apex during a reverse segment (-0.03m·s-1) every 3min. Results: The mean differences (± limits of agreement) to speed at MLSS were +1.0±4.1% (speed at 4mmol·L-1), +1.5±3.5% (modified maximum distance method), -0.2±4.7% (LM) and 2.0±3.1% (RLT). All threshold concepts showed good agreement with MLSS pace (intraclass correlation coefficient = 0.886). Conclusions: Test protocols with a fixed step duration and fine increments allowed high accuracy in estimating MLSS pace. With similar criterion agreement to the LM and RLT tests, incremental step tests appear more practicable due to less prior knowledge required and derivation of individual training zones.